PENGEMBANGAN LEMBAR KERJA SISWA BERBASIS INKUIRI TERBIMBING PADA SUBMATERI SISTEM PERNAPASAN MANUSIA KELAS XI SMA - Manisa, Tesa; Aryati, Eka; Marlina, Reni (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2017)
AbstractThis research aims to determine the validity of guided inquiry-based student worksheet on human respiratory system subdivision. The method that was used in this research was development research with 11th student grade of MIA 4 Senior High School Number 1 Pontianak on academic year 2016/2017 as the research subject with total 28 students. This research had done in two phase consist of preliminary and formative evaluation. Validation sheet was used as the techniques of data collection. Guided inquiry-based student worksheet on human respiratory system subdivision were validated by lecturer and teacher. As the research result, guided inquiry-based student worksheet on human respiratory system subdivision was declared very valid with Vc=1,00. It has four aspects, these are feasibility content, language, dish, and graphic. So it can be concluded that guided inquiry-based student worksheet on human respiratory system subdivision is very valid to be used in the learning process.                                                                             Keywords: student worksheet, guided inquiry, development research, human respiratory system